Estimation of bearing capacity of basalts at the Atasu dam site, Turkey - Alemdag, Selcuk; Gurocak, Zulfu; Solanki, Pranshoo; Zaman, Musharraf (Springer Heidelberg, 2008)
This paper describes the results of the engineering geological investigations and bearing capacity studies carried out at the proposed site of the rock fill Atasu Dam, to be constructed on basalts and pyroclastics. Rock mass strength and modulus of elasticity of the rock mass were determined using the Hoek-Brown empirical strength criterion. Rock mass classifications for the dam rock foundation were undertaken following the RMR, Q and GSI systems and the stress distributions using the finite element technique. To estimate the bearing capacity of the basalts, different empirical equations were used and compared.
Keywords: basalt; bearing capacity; Hoek-Brown empirical failure criteria